Value of silicone gel in prevention of cobblestoning following punch minigrafting in vitiligo. (2nd January 2022) - Anbar, Tag; Abd El Raheem, Talal; Bassiouny, Dalia Ahmed; Fawzy, Marwa Mohamed; El Maadawi, Zeinab; Farouk, Noha; Hassan, Mohamed
Abstract: Background: Cobblestoning is the most common complication of minipunch grafting. Objective: To assess the value of silicone gel application following minipunch grafting and the histopathological and immunohistochemical changes in cases with cobblestoning. Methods: Minipunch grafting was performed in two similar vitiligo lesions in 27 cases with stable vitiligo. After healing, silicone gel was applied twice daily on one lesion while zinc oxide ointment was applied to the other lesion serving as a control. Four biopsies were taken from each case; normal, vitiliginous skin before treatment and the two treated lesions 3 months after therapy, for histopathology and immunohistochemical staining for MMP9 & tenascin-C. Results: Repigmentation occurred in 19 cases (70.7%). The number of lesions showing excellent and good response was significantly higher on the silicone gel side ( p  < .001). In 20 cases, cobblestoning either occurred or was absent on both sides. Histopathologically, cobblestoning was similar to hypertrophic scarring. Both markers were elevated after therapy on both sides with no significant difference in percentage change between lesions showing positive and negative cobblestoning. Conclusion: Silicone gel application after minigrating improved the final response with no significant effect on the occurrence of cobblestoning. Cobblestoning resembled hypertrophic scarring histopathologically.